2007
DOI: 10.1152/ajpregu.00215.2007
|View full text |Cite
|
Sign up to set email alerts
|

Physiological genetics of dietary restriction: uncoupling the body temperature and body weight responses

Abstract: Numerous physiological and molecular changes accompany dietary restriction (DR), which has been a major impediment to elucidating the causal basis underlying DR's many health benefits. Two major metabolic responses to DR that potentially underlie many of these changes are the body temperature (T(b)) and body weight (BW) responses. These responses also represent an especially difficult challenge to uncouple during DR. We demonstrate in this study, using two recombinant inbred (RI) panels of mice (the LXS and LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…A number of recent studies have called attention to the importance of intraspecific genetic variation in response to DR [including cases when DR actually shortens lifespan (Rikke et al, 2003;Rikke and Johnson, 2007;Liao et al, 2010;Rikke et al, 2010)]. In the present study, we demonstrate that genetically based differences in MR can account for equivocal results of the studies on directional effects of DR on metabolism.…”
Section: Introductionmentioning
confidence: 44%
See 1 more Smart Citation
“…A number of recent studies have called attention to the importance of intraspecific genetic variation in response to DR [including cases when DR actually shortens lifespan (Rikke et al, 2003;Rikke and Johnson, 2007;Liao et al, 2010;Rikke et al, 2010)]. In the present study, we demonstrate that genetically based differences in MR can account for equivocal results of the studies on directional effects of DR on metabolism.…”
Section: Introductionmentioning
confidence: 44%
“…This indicates that both BMR and PMR are largely underlined by different metabolic pathways, and that they are independently affected by DR treatment (see also Rikke and Johnson, 2007). Indeed, except for the heart, changes in the masses of other metabolically active internal organs are likely to contribute to changes in BMR, rather than PMR (Książek et al, 2004;Gębczynski and Konarzewski, 2011).…”
Section: Effect Of Experimental Treatment On Pmrmentioning
confidence: 93%
“…All these effects influence heat balance and hence T b by elevating heat production. However, an additional potential effect is via increased rates of heat loss because of modulated heat dissipation, and studies in both rats and mice have concluded that this is the major factor driving strain differences in the T b response to CR (Duffy et al, 1990a,b;Rikke and Johnson, 2007). Fig.…”
Section: Body Temperature (T B )mentioning
confidence: 99%
“…The literature describing experimental undernutrition in animals is too vast to be covered here. Recent studies describing the involvement of several genes in regulating differences in the physiological adaptations to dietary restriction, however (Rikke and Johnson 2007), offer possibilities for investigating variations in the human response to fasting.…”
Section: Animal Models Of Anmentioning
confidence: 99%